Membranes Materials, Simulations, and Applications - Maciel-Cerda, Alfredo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book describes current advances in the research on membranes and applications in industry, groundwater, and desalination processes. Topics range from synthesis of new polymers to preparation of membranes using new water treatments for effluents, graphite membranes, development of polymeric and ceramic materials for production of membranes intended to separate gases and liquids, and liquid-liquid phases. The authors include materials used to produce catalytic membranes for polymer synthesis. The book also details theoretical approaches and simulation of membrane processes and parameters and design. Describes application of membranes in industry, groundwater, and desalination processes Details simulation of membrane processes and parameters and design Includes ceramic membranes, graphite membranes, and theoretical approaches.
1 Poly (Hexahydrotriazine) Membranes Prepared By Coupling Reaction between Diamines and Aldehydes -- 2 Preparation and Characterization of Hybrid Membranes Based on Poly(Ether-B-Amide) -- 3 Preparation of Membranes Based on PolySulfone (PSU) and Graphene Oxide (GrO) by Electrospinning -- 4 Ceramic Crossflow Filtration in Food and Dairy Applications -- 5 Sulfated TiO2-ZrO2 Membrane as-synthesized by Sol-Gel Method: Application in the Olefin Oligomerization -- 6 CO2/N2 Separation in Postcombustion Processes by Means of Alumina-Supported-Ionic-Liquid Membranes -- 7 Synthesis of Catalytic Membranes for the Oxidation of Organic Pollutants in Wastewater -- 8 Ion Transport through Biomimetic Nanochannel Membranes -- 9 Synergies between Pulsatile Flow and Spacer Filaments in Reverse Osmosis Modules -- 10 Obtaining the Tortuosity Factor as a Function of Crystallinity in Polyethylene Membranes -- 11 Three Dimensional Modelling, and Simulation of Multilayer Spacers for Spiral Wound Membrane Modules.-12 Biofouling Studies on Thin Film Composite Membranes in Reverse Osmosis Desalination Processes -- 13 Photo-Oxidation Treatment of the Reject Stream of a Nanofiltration Membrane System -- 14 Cleaning Strategies for a Membrane Bioreactor to Produce Permeate with a Quality Suitable for Indirect Reuse -- 15 Effect of the Transport Properties on the Design of a Plant and on the Economy of The Sweetening Process of Natural Gas Using Membranes -- 16 Fouling Modeling and Optimization of Membrane Module Design for Brackish and Sea Water Desalination in the Mexican Pacific Coast - Project Description and Progress -- 17 Research on Polymer Membranes and Teaching Performed in Unam Campus Morelia.
Keywords: Ceramic materials; Biophysics; Polymers; Ceramics; Biophysics; Polymers